Natural, Artifactual, and Evolutionary Perspective - Juricevic, Igor; Kennedy, John M. (Public Journal of Semiotics, 2008)
Looking out at the world around us, we readily perceive our 3-D surroundings. The sizes of objects in our environment, such as tiles on a piazza, distant buildings on a ground plane, tools on a tabletop, or foreground and background people in a large crowd, are perceived highly accurately, at least within a certain spatial range. So too is the layout of these objects, that is, their distances from us and from each other and their relative dimensions. The process of the visual perception of a real-world 3-D scene occurs so easily and naturally that we hardly notice how we pick up information about it by vision. Here we will describe the features on which vision relies to gain impressions of size and shape, and the approximations it accepts in assessing the 3-D spatial layout of the environment.